ANALISIS PENGARUH KNOWLEDGE SHARING DAN DISIPLIN KERJA TERHADAP KINERJA UMKM DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Yudatama, Wahyu Hamzah; Achmad, Nur (ITB AAS Indonesia Surakarta, 2024)
Employee performance is an important factor in establishing an efficient and effective MSME or organization, so an employee must have good skills to be able to meet the expected MSME criteria. The aim of this research is to determine the effect of knowledge sharing and work discipline on the performance of MSMEs with motivation as an intervening variable. The method used is SEM with a PLS approach. The results of the research obtained two data processing, namely the results of direct influence testing and the results of indirect influence testing. The results of the research resulted in testing the direct influence of work discipline which had a significant effect on performance, work discipline had a significant effect on motivation, knowledge sharing had a significant effect on performance, knowledge sharing had a significant effect on motivation. Then, in testing the indirect effect, motivation can mediate positively and but does not have a significant effect between work discipline on MSME performance and motivation can mediate positively and significantly between knowledge sharing and MSME performance